2018
DOI: 10.1007/s10623-018-0463-8
|View full text |Cite
|
Sign up to set email alerts
|

Euclidean and Hermitian LCD MDS codes

Abstract: Linear codes with complementary duals (abbreviated LCD) are linear codes whose intersection with their dual is trivial. When they are binary, they play an important role in armoring implementations against side-channel attacks and fault injection attacks. Non-binary LCD codes in characteristic 2 can be transformed into binary LCD codes by expansion. On the other hand, being optimal codes, maximum distance separable codes (abbreviated MDS) are of much interest from many viewpoints due to their theoretical and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 31 publications
0
87
0
Order By: Relevance
“…LCD codes also can be used for constructions of lattices [17]. Optimal and MDS codes that are LCD are studied in many papers (see [2], [8], [10], [12], [16], [20], [22], [23], [27], [19]).…”
Section: Introductionmentioning
confidence: 99%
“…LCD codes also can be used for constructions of lattices [17]. Optimal and MDS codes that are LCD are studied in many papers (see [2], [8], [10], [12], [16], [20], [22], [23], [27], [19]).…”
Section: Introductionmentioning
confidence: 99%
“…The following two lemmas characterize Euclidean and Hermitian LCD codes, as shown in [6,23]. Let O n and j n denote the all zeros and all ones column vectors of length n. The following simple result will be crucial so we state and prove it explicitly here.…”
Section: Euclidean Lcd Codes From Weighing Matricesmentioning
confidence: 99%
“…Jin showed that some Reed-Solomon codes are equivalent to LCD codes [16]. In [6], the authors proved that any MDS code is equivalent to an LCD code and constructed LCD Maximum distance Separable codes. Jitman et.…”
Section: Introductionmentioning
confidence: 99%